2014
DOI: 10.1142/s0219887814500315
|View full text |Cite
|
Sign up to set email alerts
|

Affine coxeter group Wa(A4), quaternions, and decagonal quasicrystals

Abstract: We introduce a technique of projection onto the Coxeter plane of an arbitrary higher dimensional lattice described by the affine Coxeter group. The Coxeter plane is determined by the simple roots of the Coxeter graph 2 () Ih where h is the Coxeter number of the Coxeter group () WGwhich embeds the dihedral group h D of order 2h as a maximal subgroup. As a simple application we demonstrate projections of the root and weight lattices of A 4 onto the Coxeter plane using the strip (canonical) projection method. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Here ℎ = + 1 is the Coxeter number. Going to the real space, the Coxeter element acts on the plane ∥ spanned by the unit vectors In (Koca, et al, 2014(Koca, et al, , 2015 we have introduced an equivalent definition of the Coxeter plane through the eigenvalues and eigenvectors of the Cartan matrix of the root system of the lattice . The eigenvalues and eigenvectors of the Cartan matrix of the group can be written as…”
Section: Projections Of the Faces Of The Voronoi And Delone Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here ℎ = + 1 is the Coxeter number. Going to the real space, the Coxeter element acts on the plane ∥ spanned by the unit vectors In (Koca, et al, 2014(Koca, et al, , 2015 we have introduced an equivalent definition of the Coxeter plane through the eigenvalues and eigenvectors of the Cartan matrix of the root system of the lattice . The eigenvalues and eigenvectors of the Cartan matrix of the group can be written as…”
Section: Projections Of the Faces Of The Voronoi And Delone Cellsmentioning
confidence: 99%
“…The group theoretical treatments of the projection of ndimensional cubic lattices have been worked out by the references (Whittaker & Whittaker, 1987;Koca et al, 2015) and a general projection technique on the basis of dihedral subgroup of the root lattices has been proposed by Boyle & Steinhardt (Boyle & Steinhardt, 2016). In a recent article (Koca et al, 2018a) we pointed out that the 2dimensional facets of the 4 Voronoi cell projects onto thick and thin rhombuses of the Penrose tilings. The third method is the model set technique initiated by Meyer (Meyer, 1972) and followed by Lagarias (Lagarias, 1996) and developed by Moody (Moody, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…. ; 4Þ are obtained by using the eigenvectors of the Cartan matrix of WðA 4 Þ and the fifth vector is chosen to be orthogonal to the rest (Koca, Koca & Koc, 2014b):…”
Section: The Coxeter-weyl Group W(b N ) and Its Maximal Subgroupsmentioning
confidence: 99%
“…Lie algebras derived from the root systems of the crystallographic groups are applied to particle physics as the symmetry of the standard model (Glashow, 1961;Weinberg, 1967;Salam, 1968;Fritzsch et al, 1973) and its embeddings into higher-rank Lie groups (Georgi & Glashow, 1974;Fritzsch & Minkowski, 1975;Gü rsey et al, 1976). As a typical example, let us consider SUð5Þ grand unified theory derived from the a 4 root system that describes the unification of strong and electro-weak interactions where the related polytopes describing the particle content project into two dimensions (Koca et al, 2014). As an application in quasi-crystallography, in a recent article (Koca et al, 2018), we have shown that the facet of the A 4 Voronoi cell is a rhombohedron and its 2-faces project into the Coxeter plane as thick and thin rhombuses of the Penrose tiling.…”
Section: Introductionmentioning
confidence: 99%